Spirituality/Religiosity as a Therapeutic Resource in Clinical Practice: Conception of Undergraduate Medical Students of the Paulista School of Medicine (Escola Paulista de Medicina) - Federal University of São Paulo (Universidade Federal de São Paulo) - Borragini-Abuchaim, Silvia; Alonso, Luis Garcia; Tarcia, Rita Lino (Frontiers in Psychology, 2021)
Introduction – The high degree of religious / spiritual involvement that brings meaning and purpose to a patients’ life, especially when they are weakened by pain, is among the various reasons to consider the spiritual dimension in clinical practice. This involvement may influence medical decisions and, therefore, should be identified in the medical history of a patient (anamnesis). Objective – To verify the opinion of undergraduate medical students of the Paulista School of Medicine – Federal University of São Paulo regarding the use of a patient’s Spirituality / Religiosity as a therapeutic resource in clinical practice. Method – Quantitative approach of the transversal analytical observational type. The sample was composed of academics’ medical program, from the first to the sixth year, regularly enrolled in 2017. Data collection was performed with a standardized questionnaire divided into three sections: sociodemographic profile; Duke University Religious Index; Spirituality / Religiosity in the clinical and academic context. Results – Participated in the survey 72% of the enrolled students, of which 61.4% had religious affiliation, 26.2% declared themselves agnostic and 12.4% atheists. All of them proposed to answer questions about the insertion of Spirituality / Religiosity in the patient care process. Through the Duke Religiosity Index, we evaluated the importance of religiosity in the student's personal life and the pertinence of religiosity as a therapeutic insertion for medical treatment. Regarding the clinical and academic context, most participants considered relevant the proposition of didactic-pedagogical actions in medical education related to the spiritual dimension of the patient. Conclusions – We conclude, through our research, that the insertion of the Spirituality / Religiosity of the patient as a therapeutic resource in clinical practice is feasible for most undergraduate students in Medicine of the Escola Paulista de Medicina – Universidade Federal de São Paulo (Paulista School of Medicine - Federal University of São Paulo). The result of the research, although it shows only the opinion of medical students at a Brazilian university, indicates that Spirituality / Religiosity is already part of the contemporary medical universe.